'Don't fall into any fake news traps!' What are the outcomes of a critical thinking skills programme on children and young people's ability to identify fake news online? - Rodgers, Louise M (2023)
Fake news is a category of disinformation linked to behaviours which are harmful to society and individuals. There is some evidence that belief in fake news tends to be more prevalent amongst young people, making this group potentially more vulnerable to its negative effects. In this study, a systematic review of the literature was undertaken. Findings revealed that much of the previous research around mitigating approaches has involved self-selecting participants of an older age group. This embedded mixed methods study aimed to build on this research with primary school pupils aged 10-11, as a population identified as potentially vulnerable to some of the effects of fake news, but with little systemic support. Research based in inoculation theory, which is analogous to medical vaccination, indicates that pre-emptive debunking of fake news, by exposing individuals to disinformation techniques, can offer some protection.